THE EFFECT OF VARIATION OF ELECTRIC CURRENT IN FLASH BUTT WELDING FOR CONNECTING THE RESULTS OF THE WIRE DRAWING PROCESS USING AISI 1080 MATERIAL ON TENSILE STRENGTH AND MICRO STRUCTURE - Andi; Aa Santosa (Universitas Majalengka, 2023)
This study aims to determine the effect of variations in electric current in SMAW welding on tensile strength and microstructure. One of the factors that affect the strength of a material is the mechanical strength of the material properties. if the material is welded, it can affect the tensile strength and structure of the material. This research uses AISI 1080 steel material with a diameter of 1.24mm which contains C = 0.083%, Si = 0.21%, Mn = 0.5%, P = 0.008%, S = 0.007%, Cu = 0.03%, Cr = 0.03%, Ni = 0.02%, B = 0.013%, Alt = 0.025%, As = 0.06%, N = 0.0038%, and O = 0.1%. Specimens were welded with varying electric currents at intervals of 25mA, starting from 700mA, 725mA, 750mA, 775mA, and 800mA using the splicing method. The tensile strength results from flash butt welding with a current of 700mA were 853.6N/mm², at a current of 725mA it was 867.7N/mm², at a current of 750mA it was 847.4N/mm², at a current of 775mA it was 881.8mA, and at a current of 800mA it was 805.3mA.